O DISCURSO MÉDICO NOS PRONTUÁRIOS CLÍNICOS - Filho, Claudio Bertolli (Intercâmbio, 2010)
In this article, we intend to show some elements which shape the production of clinic dossiers on pulmonary tuberculosis carriers whitin the 30’s and the 40’s. This medical discourse modality is defined as an instrument which acts as a mediator between knowledge and institutional interests, therefore, it should, at least in ideal terms, show objectivity through “neutrality” as well as the choice for especialized terminology. The tensions raised in face-to-face contacts between doctors and pacients, who carried a condition considered fatal at that time, and the logic revealed in such documents allow us to detect moments in which polifony and discoursive heterogeneity seem to be fundamental.